Analysis of psychological factors in obese patientes : pre an post treatment study (Revista de Psicología, 2018)
The present work study the obesity in relation to different psychological factors: the self-concept, anxious symptoms, depressive symptoms and predisposition for change, in two precise moments, at the beginning and at the end of an integral treatment of obesity, of 6 months of duration, from a perspective that rescues the group and the possible changes when different patients undergo treatment in this condition. The specific objective of the research was, in the first instance, to measure and describe the aforementioned factors in two moments: before and after the treatment, then evaluate whether there were significant differences or improvements between this moments. The instruments applied for the data collection were Verbal Scale of Self-concept, State-Trait Anxiety Questionnaire, Depression Questionnaire and a Predisposition Scale for Change. The results obtained provided elements to account for significant changes that existed in the patients, in all the psychological factors evaluated. This effect of improvement provided by a method of approaching this complex disease by qualified professionals and patients committed to the change, highlights the need to access comprehensive programs that actively seek to reverse this pathology that has become in a serious problem for global health.
Keywords: Obesity; Anxiety; Depression; Change; Treatment